Predicting cigarette use initiation and dependence in adolescence using an affect-driven exploration model - Khurana, Atika; Loan, Christopher M.; Romer, Dan (Frontiers in Psychology, 2022)
Adolescent decisions, especially in novel contexts, are often guided by affective evaluations (i.e., feelings associated with a stimulus) rather than knowledge of the risks and probabilities of different outcomes. In this study, we used the affect-driven exploration (ADE) model to illustrate how affective evaluations can play a critical role in driving early use of cigarettes, as well as the adaptive function of the resulting experiential learning in informing future affect and cigarette use. We analyzed five waves of data collected from a large, diverse community sample of adolescents who were followed from early to late adolescence (N= 386; 50.9% female; Baseline age = 11.41±0.88 years) during years 2004-2010 to model trajectories of positive affect and risk perceptions (associated with cigarette use) and examined the associations of these trajectories with their self-reported cigarette use and dependence symptoms. Consistent with the ADE model, early initiators reported higher levels of positive affect at baseline, which we argue may have led them to try cigarettes. Notably, most early initiators reported a decline in positive affect over time, suggesting an experience-based shift in affective evaluations associated with cigarette use. Risk perceptions associated with cigarette use did not emerge as a significant predictor of cigarette use or subsequent dependence. Therefore, for deterring adolescent cigarette use, efforts to influence affect (through graphic warning labels and other media) may be more effective than directly influencing risk perceptions. Despite the affective basis for initiating cigarette use, few adolescents engaged in early use (N=20) or developed symptoms of dependence (N = 25). Majority of those who engaged in early cigarette use showed a decline in positive affect, with corresponding increase in risk perceptions over time. Some early users may indeed continue to engage in cigarette use, but this is likely driven by the addictive properties of the drug. Overall these findings challenge the popular stereotype of impulsive and emotionally reactive behaviors during adolescence, and suggest a more nuanced interpretation of adolescent risk behavior.